Les Fatimides et le Maghreb central : littoralisation de la dynastie et modes de contrôle des territoires - Allaoua Amara (Revue des Mondes Musulmans et de la Méditerranée)
After chasing away the Aghlabids from Ifrīqiya, the Fatimids relocated the center of their predication, from where they ruled over the Kutāma fortresses, first in Ṣabra near Kairouan, then in Mahdia, first Islamic capital to be on the coast. A theological reform was necessary in order to define a posteriori the first ismaili centers as “territories of exile” (dār al-hijra) and to give legitimation to the imperial aims of the caliphs. This withdrawal from the Central Maghreb does not mean however that the Fatimids abandonned the region, in which they had to develop several modalities of territorial control. Resorting to Kutāma preachers, eunuchs and local influential families was one of the means they used in order to do so.